New species of the Heterodermia comosa-group (Physciaceae, lichenized Ascomycota) from southern South America - Michlig, Andrea (2017)
Fil: Michilig, Andrea. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.